Exploring Pedagogical Competencies for Transformative Teaching and the Role of Transformative Pedagogy in Higher Education: Fostering Reconnection to Self, Others, and Nature - Mariana Tolkatser (Glocality)
Education for Sustainable Development (ESD) is an emerging field in higher education focused on generating a greater level of awareness for sustainability-related matters and worldviews. However, there is a need to discover new approaches to expose learning communities to information in most effective and efficient ways. This study explores Transformative pedagogy (TP) in line with sustainable transition which emphasises transformation. It explores existing theory on the subject along with educators applying TP in their teaching practice, and new insights were drawn based on the experiences shared by the interviewees. The research shows that educators who decide in favour of transitioning towards TP, are most likely to be successful in conveying their message and enforcing transformation and change within and beyond their learning communities. This study provides a comprehensive overview of the individual and shared competencies necessary for implementing TP in higher educational settings. Moreover, this article provides limitations and risks associated with the practice.